2010
DOI: 10.1159/000298879
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Paraoxonase 1 Enzymatic Activity in Diabetic Foot Patients from Romania and Belgium: Favorable Association of High Flavonoid Dietary Intake with Arylesterase Activity

Abstract: Background/Aims: The antiatherosclerotic enzyme paraoxonase (PON1) is affected by disease and lifestyle. We investigated the impact of diet in diabetic foot patients from 2 European countries. Methods: Dietary intake and serum PON1 activity, using as substrate paraoxon (paraoxonase) or phenylacetate (arylesterase), were assessed in patients from Bucharest (n = 40) and Antwerp (n = 30) and in 34 healthy controls. Results: The diabetic patients had lower paraoxonase and arylesterase activities than the controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…Most studies were cross-sectional in design or reported cross-sectional data from cohort studies. In two studies [29, 32], data were extracted from case–control setting. Participants from 18 CEE/FSU countries and 18 WE states were included in the comparisons and most countries were covered by more than one study.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were cross-sectional in design or reported cross-sectional data from cohort studies. In two studies [29, 32], data were extracted from case–control setting. Participants from 18 CEE/FSU countries and 18 WE states were included in the comparisons and most countries were covered by more than one study.…”
Section: Resultsmentioning
confidence: 99%
“…Arylesterase activity of PON1 was determined according Eckerson et al. and Lixandru et al . using phenyl acetate (ref.…”
Section: Methodsmentioning
confidence: 99%
“…Intake of antioxidant-rich foods, like fruit and vegetable juices, affect the activity and/or concentration of PON1 [ 15 ]. In diabetic patients from two European countries, a flavonoid-rich diet was positively associated with PON1 arylesterase activity [ 72 ]. However, in healthy volunteers with adequate vitamin intake, six week diets differing markedly in the amounts of linoleic and oleic acid and vegetables, berries and apples did not differ in their effects on lipid peroxidation or lipoprotein metabolism, and all these diets decreased PON1 activity [ 73 ].…”
Section: Pon1 and Other Constituents Of Mediterranean Dietmentioning
confidence: 99%